The Influence of Religious Leaders and Faith-Based Organizations on Health Observance, Behaviors and Public Health Policies - Mike, Jennifer Heaven (Indonesian Journal of Religion and Society, 2025)
International, national, and local religious leaders and organizations' contributions to promote public health are increasingly being explored and explicated. Religious leaders and faith-based organizations can potentially play strong roles in influencing health behaviours, and compelling obedience to health policies, and health intervention measures. Importantly, they can help frame approaches that will ensure the successful implementation of health policies and measures. The central aim of this qualitative study is to explore and examine the role of religious bodies, as community gatekeepers and trusted authorities, in supporting health interventions and promoting their compliance. This study particularly focuses on the extent of their influence and the nature of the support they offer. The population for this study comprises 15 Christian and Muslim religious leaders in Yola North and South Local Government Area of Adamawa state in Nigeria who represented the views of their organizations. The questions centred on the spiritual, psychosocial, and humanitarian role they played during the peak outbreak of the COVID-19 Pandemic, the dialogues and partnerships they had with the government and health authorities, and the extent of their contribution to supporting health policies. The study finds that religious leaders can positively lend their reputation, offer guidance, and galvanize community effort to support behavioural changes, drive healthcare and ensure compliance with health measures.